First campaign of survey and excavations at Shiyāʾ (Sūr, Sultanate of Oman) - Munoz, Olivia; Azzarà, Valentina; Giscard, Pierre-Henri; Hautefort, Raphaël; Basilio, Fanny San; Saint-Jalm, Léa (Proceedings of the Seminar for Arabian Studies, 2017)
We present the results of the first fieldwork season at Shiyāʾ, near Sūr, Sultanate of Oman, carried out in January 2016. Drone aerial survey, field walking, and excavations were undertaken to obtain a first overview of the archaeological potential of the area, already known from previous research as an important protohistoric necropolis. Over 400 cairns were identified and integrated into a 3-D model of the landscape providing an accurate map. Three Hafit-type tombs, with different locations within the landscape (low and high terraces), were excavated to test the degree of preservation of the structures, grave-goods, and osteological remains. The results of this first season are very encouraging, and underline the high potential of the area. Further investigation may enable a reconsidering of a series of questions related to coastal occupations in the region. The many graves and their diversified locations might offer insights concerning the typo-chronology of the monuments, the correlation between tomb density and number of individuals per tomb (MNI), and the degree of congruence between the monumentality of the structures and the value of associated grave-goods. Furthermore, the numerous Early Bronze Age tombs suggest a long-term occupation and hint at the presence of an important settlement in the area, which would allow a more in-depth consideration of the relation between graveyards and settled areas.